Analysis of risk factors for the development of a post-bronchoscopy respiratory infection in lung cancer patients. Issue 2 (February 2021) - Shimoda, Masafumi; Yamana, Kazunari; Yano, Ryozo; Saitou, Masaoki; Fujiwara, Keiji; Furuuchi, Koji; Osawa, Takeshi; Uesugi, Fumiko; Arakawa, Kenichi; Morimoto, Kozo; Tanaka, Yoshiaki; Kokutou, Hiroyuki; et al.
Abstract: Background: The development of pneumonia following bronchoscopy is a very important post-bronchoscopic complication, while lung abscesses after bronchoscopy are rare. However, bronchoscopic techniques have advanced, and recently, we have observed patients with lung abscess after bronchoscopy. Therefore, the risk factors might vary from those in past reports. This study was performed to identify the incidence of and risk factors for post-bronchoscopy respiratory infections. Methods: We retrospectively studied adult patients diagnosed with lung cancer by bronchoscopy at Fukujuji Hospital from January 2017 to June 2019. The infection and noninfection groups were compared. The incidence of lung abscess was compared between recent periods and 2013, when endobronchial ultrasonography with a guide sheath (EBUS-GS) was not yet used in our hospital. Results: We reviewed 327 patients, including 20 patients (6.1%) with infections. The risk factors for infection were necrosis and/or a cavity in the tumor ( p  < 0.001), a large tumor diameter (≥30 mm) ( p  = 0.010), and a low serum albumin level (<4.0 g/dL) ( p  = 0.010). We developed a predictive score with these risk factors, and the area under the curve was 0.737 (95% Cl: 0.610–0.864). No significant differences in age, current smoking status, or abnormal bronchoscopic findings were observed, although these were previously reported as risk factors. In total, 12 patients had lung abscesses (3.7%), which is a higher incidence than that in 2013 (0.8%). Conclusions: The risk factors for developing post-bronchoscopy respiratory infection in our study varied from those in past reports, possibly because of the advancements in bronchoscopic techniques, such as EBUS-GS.